Neurosteroids Alter p-ERK Levels and Tau Distribution, Restraining the Effects of High Extracellular Calcium - Konsta, Vasiliki; Paschou, Maria; Koti, Nikoleta; Vlachou, Maria Evangelia; Livanos, Panteleimon; Xilouri, Maria; Papazafiri, Panagiota (International Journal of Molecular Sciences, 2024)
Neurosteroids are undeniably regarded as neuroprotective mediators, regulating brain function by rapid non-genomic actions involving interference with microtubules. Conversely, hyperphosphorylated Tau is considered responsible for the onset of a plethora of neurodegenerative diseases, as it dissociates from microtubules, leading to their destabilization, thus impairing synaptic vesicle transport and neurotransmission. Consequently, we aimed to investigate the effects of neurosteroids, specifically allopregnanolone (Allo) and dehydroepiandrosterone (DHEA), on the levels of total and phosphorylated at Serine 404 Tau (p-Tau) in C57BL/6 mice brain slices. In total tissue extracts, we found that neurosteroids elevated both total and p-Tau levels without significantly altering the p-Tau/Tau ratio. In addition, the levels of several enzymes implicated in Tau phosphorylation did not display significant differences between conditions, suggesting that neurosteroids influence Tau distribution rather than its phosphorylation. Hence, we subsequently examined the mitochondria-enriched subcellular fraction where, again, both p-Tau and total Tau levels were increased in the presence of neurosteroids. These effects seem actin-dependent, as disrupting actin polymerization by cytochalasin B preserved Tau levels. Furthermore, co-incubation with high [Ca2+] and neurosteroids mitigated the effects of Ca2+ overload, pointing to cytoskeletal remodeling as a potential mechanism underlying neurosteroid-induced neuroprotection.
CRIS-Team Scopus Importer:2024-11-22
Keywords: actin cytoskeleton; allopregnanolone; Ca; dehydroepiandrosterone; ERK phosphorylation; mitochondria; neurosteroids; Tau